Relationship between Painful Crisis and Serum Zinc Level in Children with Sickle Cell Anaemia - Edamisan Olusoji Temiye; Edem Samuel Duke; Mbang Adeyemi Owolabi; James Kweku Renner (Anemia)
Sickle cell anaemia (SCA) is associated with zinc deficiency; zinc supplementation may ameliorate some of its clinical manifestations including the relief of painful crisis. Subjects and Methods. Serum zinc levels were determined in 71 children with SCA and painful crisis and in equal numbers in steady state. Seventy-one children with AA genotype acted as controls. Qualitative assessment of zinc content of 24-hour dietary recall and the last meal consumed before blood was drawn was taken. Serum zinc was determined using atomic absorption spectrophotometer. Haemoglobin concentration and packed cell volume (PCV) were determined using standard methods. Results. The mean serum zinc concentration in the study was less than international reference range. The controls had significantly higher serum zinc concentrations than the SCA group (42.7±13.6 versus 32.3±14.0 μg/dL, P<.000); this difference was due to the significantly lower values of serum zinc in SCA with painful crisis compared with the remaining two groups F=30.9, P<.000. There was a positive correlation between serum zinc and haemoglobin concentration only in the control group (r=0.4; P=.001). Conclusion. The serum zinc levels in this study were low. Painful crisis in SCA may exert greater demand for zinc utilization in children with SCA thereby resulting in lower serum levels.